The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/adma.202005465
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Moments Induced by Atomic Vacancies in Transition Metal Dichalcogenide Flakes

Abstract: Abstract2D magnetism plays a key role in both fundamental physics and potential device applications. However, the instability of the discovered 2D magnetic materials has been one main obstacle in deep research and potential application of 2D magnetism. Here, a localized magnetic moment induced by Pt vacancies in air‐stable type‐II Dirac semimetal PtSe2 flakes is reported. The localized magnetic moments give rise to the Kondo effect, evidenced by logarithmic increment of resistance with decreasing temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Se defects will break the spatial symmetry of two surfaces of 1T sandwich structure PtSe 2 . Unlike the widely studied Pt defects which induce a local magnetic moment, [41][42][43][44]47,52,53] Se defects improve the electronic conductivity. [46,48] Note that some different Se defects even exhibit nearly same scanning tunneling microscope (STM) images, making the real structures of Se defects are very hard to be identified in experiment while Pt defects are relatively easy to identify.…”
Section: Se Defects In Monolayer Ptsementioning
confidence: 83%
See 1 more Smart Citation
“…Se defects will break the spatial symmetry of two surfaces of 1T sandwich structure PtSe 2 . Unlike the widely studied Pt defects which induce a local magnetic moment, [41][42][43][44]47,52,53] Se defects improve the electronic conductivity. [46,48] Note that some different Se defects even exhibit nearly same scanning tunneling microscope (STM) images, making the real structures of Se defects are very hard to be identified in experiment while Pt defects are relatively easy to identify.…”
Section: Se Defects In Monolayer Ptsementioning
confidence: 83%
“…However, studies on the structure and catalysis capacity of defects, especially multiple ones, in PtSe 2 are still rare. [41][42][43][44][45][46][47][48][49][50][51][52][53] In this paper, the structures, fractions and catalytic performance of various Se vacancies in defective PtSe 2 (d-PtSe 2 ) monolayers were investigated systematically. We indicate the point Se vacancies are quite stable once they are introduced in PtSe 2 .…”
mentioning
confidence: 99%
“…al. also reported the existence of magnetic moments induced by Pt vacancy defects in PtSe 2 flakes ( Ge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
“…Their work suggested that 2D monolayer nanosheets like Mn-doped CdSe(en) 0.5 had advantages for future diluted magnetic semiconductor (DMS) applications. Recently, Ge et al reported magnetic moments induced by atomic vacancies in transition metal dichalcogenide PtSe 2 flakes, and they experimentally demonstrated the presence of nearly thickness-dependent, localized magnetic moments induced by Pt-vacancy defects in air-stable PtSe 2 flakes [207]. Their work indicated that defect control was a practical approach to induce magnetism in non-magnetic materials, offering a new way to modulate magnetism in TMDCs.…”
Section: Property Manipulationmentioning
confidence: 99%